Reflections on the Socratic method. Issue 2 (1st June 2015) - Althof, Rachel Smith
The term Socratic method is often used in academic circles in a variety of syntactical contexts. This article is a detailed analysis of the historical text Alcibiades, seeking contemporary relevance with an opening anecdotal account of ongoing art critiques with a group of adolescent students. An analysis of the text shows that Socrates' genius lies in his openness to adapt to the changing landscape of dialogue. In doing so, he and his student, Alcibiades, participate in the process of askesis, or self-cultivation.